The Challenge of Integrating AI into Learning to Translate from Indonesian to Arabic: Implications for Education and Ethics: التحدي المتمثل في دمج الذكاء الاصطناعي في تعلم الترجمة من الإندونيسية إلى العربية: الآثار المترتبة على التعليم والأخلاق - Azwir, Azwir; Zulhelmi; Zulkhairi; Maulidatun Rahmi; Muhammad Yasir (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This research aims to examine the challenges related to the integration of AI into learning translation from Indonesian to Arabic, with a focus on the educational and ethical impacts resulting from this integration. The findings suggest that overcoming these challenges requires a holistic approach that combines technical and ethical awareness, while improving the quality of education and developing student skills through collaboration between various stakeholders, including governments, educational institutions and the technology industry. It also highlights the importance of finding sustainable solutions that support education, and emphasizes the need for collaborative efforts to integrate AI more effectively into translation learning. In conclusion, the research emphasizes the importance of understanding the challenges and opportunities presented by artificial intelligence, and the need to adopt integrated educational and ethical strategies to ensure that the maximum benefit is made of the potential of artificial intelligence in language education.